(untitled) (Journal of actual problems of jurisprudence, 2018)
In the article the author considers the status of the victim in criminal law and examines the issues of improving state activities to protect the rights of this subject. The author notes that the rights and obligations of the victim have traditionally been given sufficient attention in the science of criminal procedure law. He is one of the key participants in the criminal process and, accordingly, the issues of ensuring his rights and legitimate interests are regulated in detail by the Criminal Procedure Code of the Republic of Kazakhstan. Undoubtedly at the same time, that the victim is of significant interest also for the science of criminal law. Direct relationship of the victim to criminal law can be traced through the categories of «criminal offense», «crime» and «harm». The main content of the victim’s status is his right to compensation for the harm done, to restore the public relations violated by the crime. The personality of the victim often has a direct impact on the differentiation of the criminal responsibility of the guilty person, the processes of criminalization and penalization of socially dangerous acts. The author, examining the protection of the rights of the victim, considers not only criminal legislation. The article also highlights the issues of material compensation provided to victims of crimes in accordance with the new Law of the Republic of Kazakhstan «On the Compensation Fund for Victims». Key words: victim, victim of crime, compensation to the victim, restorative justice, compensation for the harm caused.